Distributed management by delegation - Goldszmidt, G.; Yemini, Y. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
This paper introduces a novel approach to distributed computing based on delegation-agents, and describes its applications to decentralize network management. Delegation agents are programs that can be dispatched to remote processes, dynamically linked and executed under local or remote control. Unlike scripted agents, delegation agent programs may be written in arbitrary languages, interpreted or compiled. They can thus be more broadly applied to handle such tasks as real-time monitoring, analysis and control of network resources. Distributed management by delegation (MbD) uses this to manage remote elements and domains. MbD provides a paradigm for distributed, flexible, scalable and robust network management that overcomes the key limitations of current centralized management schemes.